2014
DOI: 10.1016/j.mvr.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic actions of the mangosteen polyphenolic xanthone derivative α-mangostin

Abstract: Retinal neovascularization is a major cause of vision loss in diseases characterized by retinal ischemia and is characterized by the pathological growth of abnormal vessels. Vascular Endothelial Growth Factor (VEGF) is known to play an important role in this process. Oxidative stress has been strongly implicated in up regulation of VEGF associated with neovascularization in various tissues. Hence, compounds with anti-oxidant actions can prevent neovascularization. α-mangostin, a component of mangosteen (Garcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Among the plethora of plant-derived compounds having therapeutic proprieties, α-mangostin and anthothecol have elicited particular interest for antioxidant, antimicrobial, anticancer, and anti-inflammatory properties [113][114][115][116][117]. The α-mangostin was found to suppress EMT by inhibiting MMP2 and MMP9 and increasing E-cadherin expression by downregulating the PI3K/Akt pathway [118].…”
Section: α-Mangostin and Anthothecolmentioning
confidence: 99%
“…Among the plethora of plant-derived compounds having therapeutic proprieties, α-mangostin and anthothecol have elicited particular interest for antioxidant, antimicrobial, anticancer, and anti-inflammatory properties [113][114][115][116][117]. The α-mangostin was found to suppress EMT by inhibiting MMP2 and MMP9 and increasing E-cadherin expression by downregulating the PI3K/Akt pathway [118].…”
Section: α-Mangostin and Anthothecolmentioning
confidence: 99%
“…Other studies also showed these mechanisms of action of this compound, suggesting that it can be considered a potential chemopreventive agent as it inhibits cell proliferation, inducing apoptosis and cell cycle arrest, modulating phase I and phase II enzymes, especially downregulation cyclins/cyclin‐dependent kinases (CDKs) . It can also act in carcinogenesis by preventing angiogenesis and metastasis progression, reducing the expression of vascular endothelial growth factor (VEGF) and the expressions of matrix metalloproteinase (MMP)‐2 and MMP‐9, and blocking the invasion and metastasis of various cancers . Recently, Markowicz et al .…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In addition, α-MG inhibited VEGF-mediated biological effects by interfering with VEGF signaling pathways. Jittiporn et al [102] found that α-MG dramatically and dose dependently suppressed VEGF-induced hyperpermeability, increased proliferation, migration, and tube formation in retinal endothelial cells, and limited vascular sprouting in the ex vivo aortic ring assay through suppressing VEGF-induced phosphorylation of VEGFR2 and ERK1/2 (a major downstream target of VEGFR2). Another study reported on its inhibitory effects on VEGF-induced proliferation, migration, and tubule formation of human umbilical vein endothelial cells [103].…”
Section: Suppression Of Angiogenesismentioning
confidence: 99%
“…Human breast cancer MCF-7 cell [94] Inhibition of angiogenic and metastatic progression VEGF expression↓ Breast cancer T47D cells [99] VEGF-A/SDF-1 secretion↓ Activated pancreatic stellate cells [101] VEGFR2↓, EKR1/2↓ Retinal microvascular endothelial cells [102] Phosphorylation of VEGFR2↓ Human umbilical vein endothelial cells [103] MMP-2/MMP-9/NF-κB/Akt1 expression↓ Human melanoma SK-MEL-28 cells [105] MMP-2/NF-κB expression↓, IκBα expression↑ Human squamous cell carcinoma A-431 cells [106] continued…”
Section: Molecular Modeling and Docking Studymentioning
confidence: 99%